PENGGUNAAN PENDEKATAN PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN (PKn) - Hendrawati, Hendrawati (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
Based on the observations SDN 07 Lasi Tuo that students get to learn a  result. The purpose  this study was to  the use cooperative learning approach type Numbered Head Together (NHT) to improve student learning  education in the elementary school classroom V 07 Lasi Tuo, District Canduang, Agam District This study used a qualitative approach and quantitative approach to the shape the  study to look at the use the cooperative learning approach Numbered Head Together (NHT) in learning Civics. This study was conducted SDN 07 Lasi Tuo with subjects is a class V SD. Data were analyzed using qualitative data analysis. The results showed in student learning of preliminary tests before the study  is 40. After the first of the increased to 74 meetings and meetings of 2 to 75.67. After the  improving student learning  with the class average to 87. It can be using the type cooperative Numbered Head Together (NHT) to improve student learning outcomes.   Kata kunci     : pendekatan pembelajaran kooperatif, meningkatkan hasil belajar